Principles Governing Control of Aggregation and Dispersion of Graphene and Graphene Oxide in Polymer Melts. Issue 36 (28th July 2020) - Suter, James L.; Sinclair, Robert C.; Coveney, Peter V.
Abstract: Controlling the structure of graphene and graphene oxide (GO) phases is vitally important for any of its widespread intended applications: highly ordered arrangements of nanoparticles are needed for thin‐film or membrane applications of GO, dispersed nanoparticles for composite materials, and 3D porous arrangements for hydrogels. By combining coarse‐grained molecular dynamics and newly developed accurate models of GO, the driving forces that lead to the various morphologies are resolved. Two hydrophilic polymers, poly(ethylene glycol) (PEG) and poly(vinyl alcohol) (PVA), are used to illustrate the thermodynamically stable morphologies of GO and relevant dispersion mechanisms. GO self‐assembly can be controlled by changing the degree of oxidation, varying from fully aggregated over graphitic domains to intercalated assemblies with polymer bilayers between sheets. The long‐term stability of a dispersion is extremely important for many commercial applications of GO composites. For any degree of oxidation, GO does not disperse in PVA as a thermodynamic equilibrium product, whereas in PEG dispersions are only thermodynamically stable for highly oxidized GO. These findings—validated against the extensive literature on GO systems in organic solvents—furnish quantitative explanations for the empirically unpredictable aggregation characteristics of GO and provide computational methods to design directed synthesis routes for diverse self‐assemblies and applications. Abstract : Controlling the dispersion and aggregation of graphene oxide (GO) is critical for harnessing its potential in many applications. This can be challenging as many competing factors contribute to its behavior in solution, and they are poorly understood. Using multiscale simulation, the key factors governing this behavior are mapped out and a framework for controlling the morphology of GO is proposed.